Management of Local Broadcast Production and Enforcement of P3SPS by Indosiar Ambon TV - Sopacua, Yustina; Alfredo, Ronald; Tahalele, Olivia (International Journal of Global Sustainable Research, 2023)
The research investigates management of local broadcast production and P3SPS (Broadcasting Code of Conduct and Broadcast Program Standards) enforcement by Indosiar TV. Four stakeholders were interviewed: Indosiar TV Ambon representatives, KPID [Regional Indonesian Broadcasting Commission] Maluku Chairperson, P3SPS Department, and community members. Primary data collected through interviews and documentation; secondary sources included web, social media, books, and journals. Research process involved pre-research media observation, field research, data categorization, and objective conclusions. Aimed at benefiting the community by preventing policy duplication and aiding grassroots execution in broadcasting.